Research methods for business : a skill-building approach - Sekaran, Uma.; Bougie, Roger (Chichester : Wiley, 2010)
"Research Methods for Business: A Skill Building Approach is a conci se and straightforward introduction for students to the world of busine ss research. The skill building approach provides students with practic al perspectives on how research can be applied in real business situati ons. Maintaining Uma Sekaran's popular and accessible style of writing, Roger Bougie draws upon his extensive experience of the field to prese nt an up-to-date guide on business research for the aspiring future man ager." "The fifth edition has a new chapter on qualitative data analysi s, featuring a case study of the research process. The chapters on scie ntific investigation, the broad problem area and defining the problem s tatement, measurement of variables, experimental designs, sampling, and quantitative data analysis have all been substantially revised. Additi onal real-life cases have been included and examples are taken from Eur ope, Asia and the US to give students a comprehensive view of modern bu siness research methods."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Business -- Research -- Methodology